2010
DOI: 10.2175/193864710798170531
|View full text |Cite
|
Sign up to set email alerts
|

Wet-Weather Pilot Studies Demonstrate Effectiveness of High-Rate Filtration Technologies

Abstract: Like many communities across the United States, Johnson County, Kansas and the City of St. Joseph, Missouri, are considering means to control collection system overflows from their publicly owned treatment works while maintaining or improving water quality. Planning studies for both communities evaluated several wet-weather treatment alternatives and included benchscale and pilot trials of the following processes during actual wet-weather peak flow conditions:(1) chemically enhanced sedimentation, (2) ballaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The Columbus project was partially funded by the United States Environmental Protection Agency (USEPA), which considers CMF to be an innovative technology for wet-weather management (USEPA, 2008). Wet-weather pilot studies conducted in Kansas and Missouri in 2008 and 2009 compared CMF side-by-side to other high-rate filtration alternatives as well as high-rate sedimentation alternatives and further substantiated CMF as a viable alternative for wet-weather treatment applications (Fitzpatrick et al, 2010).…”
Section: Technology Overviewmentioning
confidence: 93%
“…The Columbus project was partially funded by the United States Environmental Protection Agency (USEPA), which considers CMF to be an innovative technology for wet-weather management (USEPA, 2008). Wet-weather pilot studies conducted in Kansas and Missouri in 2008 and 2009 compared CMF side-by-side to other high-rate filtration alternatives as well as high-rate sedimentation alternatives and further substantiated CMF as a viable alternative for wet-weather treatment applications (Fitzpatrick et al, 2010).…”
Section: Technology Overviewmentioning
confidence: 93%
“…Recent side-by-side wet-weather pilot studies found that the CMF technology consistently produced effluent with lower TSS concentrations than the cloth media technology and appeared to be less sensitive to influent hydraulic and solids loading rates (Fitzpatrick et al, 2010b). Subsequent piloting of the CMF technology over multiple wet weather events confirmed that the CMF technology consistently produced effluent TSS concentrations meeting secondary treatment standards, and that the CMF effluent was consistently amenable to hypochlorite or UV disinfection at doses and contact times equivalent to those typically used for conventional secondary effluents (Fitzpatrick et al, 2010b and2011). For peak wet-weather solids loadings, design hydraulic rates of 10 to 15 gpm/ft 2 (14,000 to 20,000 gpd/ft 2 ) are generally achievable before the backwash frequency becomes unmanageable.…”
Section: High-rate Filtrationmentioning
confidence: 99%